2007
DOI: 10.1117/1.2790919
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser scanning microscopy of retinal rod outer segment intact disks: new labeling technique

Abstract: Abstract. Vertebrate retinal rod outer segment disks house the proteins involved in the phototransduction cascade that converts light into neuronal signal. We develop a technique for the immunofluorescent labeling of osmotically intact isolated rod outer segment disks for confocal laser scanning microscopy imaging. Osmotically intact Ficoll-flotation isolated bovine disks are directly labeled with antibodies in solution. For the first time, osmotically intact single disks can be visualized. Thus, imaging of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Biochemical assays, Western Blot analysis, Confocal Laser Scanning (CLSM) and Transmission Electron Microscopy (TEM) of purified Intact Myelin Vesicles (IMV) showed that IMV are able to produce ATP through the operation of a H ? gradient across their membranes [16,17]. Oximetric measurements showed that IMV consume O 2 at a rate comparable to that of mitochondria [15].…”
Section: Evidence For a Role Of Myelin In Oxidative Phosphorylationmentioning
confidence: 97%
“…Biochemical assays, Western Blot analysis, Confocal Laser Scanning (CLSM) and Transmission Electron Microscopy (TEM) of purified Intact Myelin Vesicles (IMV) showed that IMV are able to produce ATP through the operation of a H ? gradient across their membranes [16,17]. Oximetric measurements showed that IMV consume O 2 at a rate comparable to that of mitochondria [15].…”
Section: Evidence For a Role Of Myelin In Oxidative Phosphorylationmentioning
confidence: 97%
“…Panel B1 shows that the visual pigment is uniformly distributed on disks, as previously reported. 13 Panel B2 shows the transmission image of the same disk sample merged to the fluorescence of a Cy5-labeled secondary Ab bound to an Ab against R1 subunit of Na + /K + - ATPase. The low immunoreactivity suggests a little RIS contamination.…”
Section: Assessment Of Purity Of the Disk Preparationsmentioning
confidence: 99%
“…8,9 In past years we have investigated adenosine triphosphate ͑ATP͒ production in the ROS. 10 Recently, we reported a new protocol for the imaging of disks for immunofluorescence confocal laser scanning microscopy ͑CLSM͒, 11 and the first comprehensive proteomic analysis of purified rod disks, which were obtained by combining the results of 1-D or 2-D gel electrophoresis separation of disk proteins to matrix-assisted laser desorption/ionization-time-of-flight ͑MALDI-TOF͒ or liquid chromatography electrospray ionisation tandem mass spectrometry ͑nLC-ESI-MS/MS͒ mass spectrometry techniques. Proteins involved in vision as well as in aerobic metabolism were found, among which were the five complexes of oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%